2011
DOI: 10.1186/cc10059
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of programmed death-1 on T cells and programmed death ligand-1 on monocytes in septic shock patients

Abstract: IntroductionStudies on the role of programmed death-1(PD-1) and its main ligand (PD-L1) during experimental models of sepsis have shown that the PD-1/PD-L1 pathway plays a pathologic role in altering microbial clearance, the innate inflammatory response and accelerated apoptosis in sepsis. However, the expression of PD-1 and PD-L1 and their role during the development of immune suppression in septic patients have not been elucidated. The present study was designed to determine whether the expression of PD-1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
177
4
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(197 citation statements)
references
References 38 publications
12
177
4
4
Order By: Relevance
“…However, PD-1 is also thought to be a marker of T cell aging in humans and mice (31). Our findings show increased expression of PD-1 on CD4+ and CD8+ T cells in elderly patients with sepsis when compared with that of elderly HDs, which is consistent with a previous report that PD-1 on T cells and programmed death ligand-1 (PD-L1) on monocytes are dramatically upregulated in a cohort of patients with septic shock (32). Interestingly, it has been suggested that PD-1/PD-L1 might be a therapeutic target to reverse immunosuppression in sepsis.…”
Section: Discussionsupporting
confidence: 94%
“…However, PD-1 is also thought to be a marker of T cell aging in humans and mice (31). Our findings show increased expression of PD-1 on CD4+ and CD8+ T cells in elderly patients with sepsis when compared with that of elderly HDs, which is consistent with a previous report that PD-1 on T cells and programmed death ligand-1 (PD-L1) on monocytes are dramatically upregulated in a cohort of patients with septic shock (32). Interestingly, it has been suggested that PD-1/PD-L1 might be a therapeutic target to reverse immunosuppression in sepsis.…”
Section: Discussionsupporting
confidence: 94%
“…Hence, it has been postulated that anti-PD-1 and anti-PD-L1 therapies could have similar beneficial effects in patients suffering from sepsisinduced immune dysfunction (115). Patients with severe sepsis show increased levels of PD-1 and PD-L1 on their monocyte and T lymphocyte populations (116). Recent studies demonstrated neutrophil PD-L1 upregulation on neutrophils from septic mice and humans, resulting in the potentiation of lymphocyte apoptosis through contact inhibition, which correlated with outcome (117).…”
Section: Potential Immune-modulatory Therapiesmentioning
confidence: 99%
“…Patients with sepsis whose cells demonstrate increased cell surface inhibitory molecule expression are at increased risk for secondary infections and mortality, providing evidence for another distinguishing marker of immune suppression. 47,48 Last, regulatory T cells are a highly immunosuppressive subset of T cells that are known to produce large quantities of anti-inflammatory cytokines. They appear to be resistant to apoptosis and can predominate in the subacute phase of sepsis in adults 49 although this has not been seen in children.…”
Section: Treatment-related Factorsmentioning
confidence: 99%